Risk factors of postthrombotic syndrome before and after deep venous thrombosis treatment. (July 2017) - Strijkers, Rob HW; de Wolf, Mark AF; Wittens, Cees HA
Postthrombotic syndrome is the most common complication after deep venous thrombosis. Postthrombotic syndrome is a debilitating disease and associated with decreased quality of life and high healthcare costs. Postthrombotic syndrome is a chronic disease, and causative treatment options are limited. Prevention of postthrombotic syndrome is therefore very important. Not all patients develop postthrombotic syndrome. Risk factors have been identified to try to predict the risk of developing postthrombotic syndrome. Age, gender, and recurrent deep venous thrombosis are factors that cannot be changed. Deep venous thrombosis location and extent seem to predict severity of postthrombotic syndrome and are potentially suitable as patient selection criteria. Residual thrombosis and reflux are known to increase the incidence of postthrombotic syndrome, but are of limited use. More recently developed treatment options for deep venous thrombosis, such as new oral factor X inhibitors and catheter-directed thrombolysis, are available at the moment. Catheter-directed thrombolysis shows promising results in reducing the incidence of postthrombotic syndrome after deep venous thrombosis. The role of new oral factor X inhibitors in preventing postthrombotic syndrome is still to be determined.